Management of patients with ventriculoperitoneal shunts in breast surgeries - Osama Darras; Sara Yacoub; Diwakar Phuyal; Steven Bernard; Raffi Gurunian; Sarah N. Bishop (JPRAS Open)
Ventriculoperitoneal (VP) shunts often pass through the anterior chest involving the breast parenchyma. Operating on patients with VP shunts necessitates extra caution during breast surgeries. We report two cases of female patients with VP shunts who underwent breast surgeries. We narrate the systematic approach to preserve the shunt as well as the role of interprofessional collaboration and imaging in treating these patients.